A Study of the Employment of Denial During a Complex and Unstable Crisis Involving Multiple Actors. (July 2016) - Bamber, Matthew; Parry, Simon
The authors review the use of denial through a complex and unstable crisis: the Deepwater Horizon tragedy in the Gulf of Mexico. Denial is typically viewed as a binary response—"we did not do this"—with a binary intended outcome—"and therefore we are not to blame." The authors argue that this interpretation is overly simplistic. They found that Transocean and Halliburton executed a strategy consisting of distancing and (counter)attack to shift blame, whereas BP pursued a strategy dominated by compassion and ingratiation intermixed with carefully used denial to share blame. This form of blame sharing is a hybrid of denial and acceptance. BP accepted responsibility but argued that others were responsible too. The authors' analysis also shows that deny response options were restricted or relaxed dependent on situational and intertextual context. They find that the tone of the involved parties' releases became significantly more aggressive as the situation developed toward its legal conclusion and as they responded to one another's progressively more hostile releases.